THE COGNITIVE PROCESS OF DIFFERENT GENDER IN WRITING ARGUMENTATIVE TEXT - Surya Setiadi Tarigan; I Wayan Dirgeyasa; Rahmad . Husein (LINGUISTIK TERAPAN, 2021)
The aim of this study was to know the cognitive process manner of different gender in writing argumentative text. The population of this study was grade XII of Free Methodist Senior High School Medan in 2019/2020 academic years and the sample was three males and three females. The sample was taken by snowball technique. This study was conducted by using descriptive qualitative research design of which data were the transcript of think aloud protocol and retrospective interview. In analyzing the data, this research used model of Miles and Huberman, namely data collection, data reduction, data display, and data verification. Based on the data analysis was found that male and female had difference manners in writing argumentative text. The male students generated the ideas by brainstorming, and then they outlined the thinking ideas orderly as a guide in writing. In the translating process, they tended to transform the ideas based on the generic structure of argumentative text referred to the outlines which were made before. In the process of writing they did reading and editing words and sentences have been arranged well. In the end of their writing, they tended to read their writing result to make sure. While the female students had different way with male students where in the planning process, they generated the ideas by brainstorming then, they developed the points by outlining the ideas and the ideas were improved the quality by reading and revising the ideas. In the translating process, they tended to develop their writing by structuring it based on the argumentative generic structure without reading and editing because they tended to write it fluently. In reviewing, they did reading the text to check all words and sentences. In addition, they revised the error words and sentences which were found.Keywords: Cognitive Process, Different Gender, Writing, Argumentative Text